PWE-084 Itu escalation and renal replacement therapy in decompensated liver disease – utility or futility. (22nd June 2015) - Zahid, A; Choudhury, M; Eross, B; Williams, E; White, N; Al-Shamma, S
Abstract : Introduction: Liver-related mortality continues to increase in the UK with alcohol remaining the leading cause. A recent NCEPOD report highlighted deficiencies in the acute care received by patients with decompensated ALD, including early management and access to specialist review and ITU care. In our instituition, a large DGH, we have a dedicated HDU/ITU and 2 hepatologists. We sought to assess outcomes and predictors of survival of patients admitted to ITU with decompensated CLD and utility of mechanical ventilation (MV) and renal replacement therapy (RRT.) Method: We interrogated a prospective ITU-admissions database and identified 64 patients with decompensated CLD of any aetiology admitted bewteen 2008 and 2013. We conducted a case note analysis collecting data on demographics, aetiology of CLD, cause for decompensation, Child–s and MELD scores, interventions received and 30-day and 1-year mortality. We compared outcome to previous study between 2003–07. Results: Of 64 patients, 42 (66%) were male. 55 (86%) had ALD. Mean age was 47.7 for ALD and 50.8 for non-ALD. The most common precipitant was UGI bleed (27%), sepsis (20%) and alcoholic hepatitis (17%). AKI was present in 32 (50%; 55% ALD vs 22% non-ALD; p < 0.05.) The Child–s score was A in 4 (6%), B in 9 (14%) and C in 42 (80%). The mean MELD score was higher in ALD (27) vs non-ALD patients (22.) The mean creatinine and bili were both higher in ALD vs non-ALD (51 vs 109 and 184 vs 84 respectively.) 29/55 (53%) patients with ALD had prior contact with hepatology services vs 7/9 (79%) for non-ALD. 28 patients (44%) were ventilated and 10 (16%) received RRT (all ALD patients.) The 30-day mortality was 58% for ALD and 66% for non-ALD with 1-year mortalities of 71% and 77%. Overall, survival to hosptial discharge was 20/64 (31%). The best predictor of survival was escalation to ITU within 48 h 17/24 (71%) vs 7/40 (17.5%) (p-value <0.05.) ALD patients >60 did not survive. Prognosis was better if previously under hepatology service. Receiving either MV or RRT were not predictive of a worse prognosis. As expected, higher MELD score also predicted poorer outcome. Overall survival of ALD patients of 40% over this study period is favourable compared the previous study period (29%). There was an increase in the number of admissions from 35 to 55 patients over the same period. Conclusion: Outcomes for patients with decompensated CLD including ALD are improving and ITU escalation should be offered early to all appropriate patients. Ventilation or RRT should be considered as not always predictive of poor outcome. The best chance for survival was in patients escalated within 48 h and those who had been been under the care of hepatology prior to presentation. Disclosure of interest: None Declared.